2000
DOI: 10.1046/j.1469-8137.2000.00610.x
|View full text |Cite
|
Sign up to set email alerts
|

Fungal species‐specific responses of ectomycorrhizal Scots pine (Pinus sylvestris) to elevated [CO2]

Abstract: Ectomycorrhizal seedlings of Scots pine (Pinus sylvestris) inoculated with the nitrotolerant Laccaria bicolor and the nitrophobic Suillus bovinus were exposed to ambient (350 µl l −" ) and elevated (700 µl l −" ) [CO # ]. After 79 d the seedlings were labelled for 28 d with "%CO # , after which they were harvested. "%C was determined in shoots, roots plus mycorrhizas, soil, and below-ground respiration ; nitrogen was determined in shoots and roots. Total net "%C uptake increased under elevated [CO # ]. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
49
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 16 publications
4
49
1
Order By: Relevance
“…We concluded that the carbosorb traps were most likely leaky, because respiration data are normally an order of magnitude larger (Gorissen et al 1991;Andersen and Rygiewicz 1995). Therefore, no data on below-ground respiration and below-ground carbon use efficiency (Gorissen and Kuyper 2000) are reported.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…We concluded that the carbosorb traps were most likely leaky, because respiration data are normally an order of magnitude larger (Gorissen et al 1991;Andersen and Rygiewicz 1995). Therefore, no data on below-ground respiration and below-ground carbon use efficiency (Gorissen and Kuyper 2000) are reported.…”
Section: Resultsmentioning
confidence: 94%
“…In their study, there were no significant differences in hyphal length between both species (although S. bovinus tended to form more mycelium), but pine seedlings colonized by S. bovinus had significantly higher N concentrations in shoots and roots, being above deficiency levels in the former case, and below deficiency levels in the latter. One important point if one wants to compare the results of this study with that by Gorissen and Kuyper (2000) is the duration of the experiment; in the present experiment it lasted 2 months longer, thereby increasing N-limitation due fungal and plant growth. Calculations, based on the data in Gorissen and Kuyper (2000) showed that S. bovinus transferred significantly more N per g ECM than L. bicolor; N-uptake efficiency for the former species was 20 and was reduced to 11 under elevated CO 2 , for the latter species 12 and slightly reduced to 11 under elevated CO 2 .…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Godbold and Berntson [29] suggested that higher supply of C to roots under elevated CO2 promoted the occurrence of ectomycorrhizal morphotypes with a higher production of hyphae and rhizomorphs. The idea that some ectomycorrhizal fungi can preferentially benefit from a high C supply to the roots was supported by the observation that Suillus bovinus (L.) Roussel and Laccaria bicolor respond differently in the way that they partition assimilates between fungal biomass and respiration under elevated CO2 [30]. However, these investigations under controlled conditions have been carried out on young tree seedling or saplings, which often are colonised by a restricted number of ectomycorrhizal species.…”
Section: Introductionmentioning
confidence: 99%
“…The diversity of ECM fungi is high, with estimates of over 7 000 species worldwide, associating with approximately 8 000 plant species (Rinaldi et al, 2008;Wang and Qiu, 2006), leading to research efforts into the degree of functional diversity within ECM fungi. It is known, for example, that different species of ECM fungi can access alternative nitrogen sources (Lilleskov et al, 2002b), and that certain ECM species may play a role in the decomposition of organic carbon (Chapela et al, 2001); some fungi confer more benefit to their host than others under certain environmental conditions (Gorissen and Kuyper, 2000;Johnson et al, 1997), and different species of fungi can have different carbon requirements from the host (Bidartondo et al, 2001; Fransson * Corresponding author: f.cox06@imperial.ac.uk et al, 2007). Therefore, the biodiversity of ECM fungi in any given forest is likely to have direct implications for host tree health, carbon and nitrogen cycling, and the resiliency of forest functional biodiversity.…”
mentioning
confidence: 99%